Attitudes towards COVID-19 mitigation measures implemented at St Mark's Bowel Cancer Screening Centre: a cross-sectional analysis of survey data from an ethnically diverse region in London. (November 2021) - Prentice, Andrew; Kayal, Ghalial; Marshall, Sarah; von Wagner, Christian; Kerrison, Robert S
Abstract: Background: Negative attitudes towards, and experiences with, health services can negatively affect attendance at diagnostic investigation. Since services resumed in June, 2020 (ie, following the first months of the COVID-19 pandemic), several new procedures to reduce COVID-19 transmission have been implemented, but the extent to which these measures are acceptable to patients has not yet been examined. We aimed to assess patient attitudes towards the measures implemented within St Mark's Bowel Cancer Screening Centre, St Mark's Hospital, Harrow, UK. Methods: We surveyed patients who underwent colonoscopy after their procedure and asked a series of questions using the five-point Likert scales. Factor analysis was used to group questions into mutually exclusive groups, with three factors were subsequently identified: attitudes towards measures to reduce hospital-based COVID-19 transmission (factor 1; five items), attitudes towards precolonoscopy COVID-19 swabbing (factor 2; two items), and attitudes towards protective clothing (factor 3; two items). Scales ranged from five to 25 for factor 1 and two to ten for factors 2 and 3 (with higher scores representing more positive attitudes). Descriptive statistics were used to calculate means, whereas linear regression was used to test associations between participant demographics, COVID-19 anxiety, and bowel cancer anxiety with attitudinal factors. Participation in the study was voluntary and consent was obtained from all participants. Findings: Of the 408 patients invited, 288 patients (71%) who underwent colonoscopy between July 1, 2020, and May 1, 2021, were surveyed. Participants were predominantly men (n=182; 63%) and of White (n=167; 58%) or South Asian ethnicity (n=59; 20%; the mean age of all participants was 66·52 years [SD 5·29]). The mean score was 23·12 for factor 1, 7·60 for factor 2, and 8·15 for factor 3. South Asian adults were less positive towards measures to reduce COVID-19 transmission (factor 1; 23·04) than White adults (23·18; β coefficient 0·31; p=0·035). COVID-19 anxiety was the only predictor of attitudes towards protective clothing (factor 3), with higher COVID-19 anxiety being associated with more positive attitudes towards protective clothing (0·25; p=0·037). Interpretation: Attitudes towards COVID-19 prevention measures were highly positive. Future service evaluation should focus on reassuring South Asian patients of measures to reduce hospital-related infection (eg, through information provision). South Asian patients are more likely to be diagnosed at a later stage, so reducing barriers to diagnosis to prevent COVID-19 from widening inequalities in cancer even further is imperative. Funding: This study was funded by St Mark's Bowel Cancer Screening Centre. RSK is supported by a Cancer Research UK Population Research Fellowship (C68512/A28209).